(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the success of students’ learning of basketball skills usingModern means for this, and the researcher decided to use the means of presenting skills to students aboutThe way to the computer (100m18) and a cable to a TV set to display my shooting skillsOn the basket from the front and the speed of passing the ball, the researcher assumed that the experimental group isBetter in learning the two skills than the control group that learned the two skills using the methodtraditional for learningThe researcher used (15) students for his experimental group and (15) students for his control groupThe students were randomly selected from the sixth grade students, ages (11-12 years).An educational approach was used for a period of (6 weeks), before which a pre-test and after the end of the period were conductedA post-test was conducted, and the researcher used statistical methods.